Personal Values, Ethical Behavior And Trust: External Auditor Perspective - Agung Prasetyo Nugroho Wicaksono; Firda Ayu Amalia (Jurnal Reviu Akuntansi dan Keuangan, 2022)
This study aims to analyze the impact of linear personal values on the ethical behavior of auditors and ethical behavior on trust. The research method applied in this study is a quantitative method with SEM-PLS with a confirmatory factor analysis (CFA) approach through first order and second order CFA. Data analysis using SMART-PLS 3. There are two results in this study. The results of the first study show that the ethical behavior of auditors is not influenced by personal values. The result of the second study is that ethical behavior affects auditor trust. The limitation of this research is that the data used is limited to respondents in one KAP. Future research is expected to be able to diversify respondents from various KAPs.